2021
DOI: 10.1093/cid/ciaa1935
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Longitudinal Serosurvey of Healthcare Workers in the First Wave of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Pandemic in a Quaternary Care Hospital in Munich, Germany

Abstract: Background High infection rates among health care personnel in an uncontained pandemic can paralyze health systems due to staff shortages. Risk constellations and rates of seroconversion for health care workers during the first wave of the SARS-CoV-2 pandemic are still largely unclear. Methods Health care personnel (n=300) on different organizational units in the LMU Munich University Hospital were included and followed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
(27 reference statements)
1
28
0
1
Order By: Relevance
“…High-risk exposures in hospitals can be minimized by strictly enforcing patients and staff to wear appropriate personal protective equipment (PPE), testing patients for acute SARS-CoV-2 infection upon admission and rapid isolation of suspected COVID-19 cases in separate rooms. In the hospital complex surveyed here, the ER implemented these measures early on, possibly explaining the low seropositivity among these HCWs, despite the ER being a common entry point for symptomatic COVID-19 patients into hospitals [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-risk exposures in hospitals can be minimized by strictly enforcing patients and staff to wear appropriate personal protective equipment (PPE), testing patients for acute SARS-CoV-2 infection upon admission and rapid isolation of suspected COVID-19 cases in separate rooms. In the hospital complex surveyed here, the ER implemented these measures early on, possibly explaining the low seropositivity among these HCWs, despite the ER being a common entry point for symptomatic COVID-19 patients into hospitals [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large hospital in Spain, cumulative prevalence of SARS-CoV-2 infection was reported with 11.2%, yet neither the professional category nor daily patient contact or working in COVID-19 units was identified as a risk factor for infection [ 37 ]. However, some hospitals indeed reported a higher SARS-CoV-2 prevalence for example in housekeeping staff or employees with high exposure to (COVID-19) patients [ 8 , 11 , 38 , 39 ]. For example, a study conducted in more than 3000 employees of a large health care provider in Sweden and Denmark identified the number of patient contacts during a workday as the most prominent predictor for seropositivity (2.8% in Denmark and 8.3% in Sweden).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Weinberger et al reported that HCW on both COVID-19 and regular non-COVID-19 wards had a greater rate of seroconversion than non-frontline personnel. Moreover, both the intensity and number of risk contacts were associated with seropositivity in their study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations